Communicating with people with dementia - James McKillop; Carlo Petrini (Istituto Superiore di Sanità, 2011)
It can be very difficult to communicate with people with dementia. Each case requires its own unique handling. Not every scenario is covered, as many times your own judgment is what will work, best according to the circumstances. These can change from dawn to evening and from day to day. Never assume things will be the way they were the last time you communicated. Be on your guard. Be adaptable. The article will help get you started to think of your own ways to communicate.